PENGARUH PENGALAMAN MAGANG, INFORMASI KERJA, DAN KEAHLIAN AKUNTANSI TERHADAP KESIAPAN KERJA MAHASISWA AKUNTANSI - Alam, Rindu; Susti, Nanda (Jaksya: Jurnal Akuntansi Syariah, 2025)
The purpose of this study was to investigate how internship experience, job information, and accounting expertise affect the work readiness of accounting students at UIN Sunan Ampel Surabaya, with self-efficacy as a moderating variable. With primary and secondary data, this study used a quantitative approach. Accounting program students at UIN Sunan Ampel Surabaya were the subjects of this study. This study involved all Accounting students of the Faculty of Islamic Economics and Business, UIN Sunan Ampel Surabaya, totaling 515 people. This study took a sample of 241 active accounting students from the 2019 and 2020 intakes. Data collection for this tool was carried out using a questionnaire that can be accessed online through the Google Forms application. This study uses Moderate Regression Analysis (MRA) with the help of the SPSS program. The findings of this study indicate that accounting expertise affects the work readiness of accounting students and internship experience affects the work readiness of accounting students. Meanwhile, job information does not affect the work readiness of accounting students. The research findings also revealed that self-efficacy can moderate the relationship between accounting skills and internship experience on accounting students' work readiness, but does not moderate the relationship between job information and accounting students' work readiness.